Endoscopic transforaminal lumbar interbody fusion without general anesthesia: technical innovations and outcomes - Kolcun, John Paul G.; Brusko, G. Damian; Wang, Michael Y. (Annals of Translational Medicine, 2019)
Innovations in surgical techniques and technologies have enabled spine surgeons to offer patients less morbid alternatives to traditional spine procedures. This review will explore the development of the endoscopic transforaminal lumbar interbody fusion (TLIF) without general endotracheal anesthesia (GETA) and discuss the technical refinements and innovations learned from experiences with this technique. The Awake TLIF employs several key technological innovations: (I) conscious sedation; (II) endoscopic visualization; (III) an expandable interbody device; (IV) recombinant human bone morphogenetic protein; (V) long-acting local analgesia; and (VI) percutaneous instrumentation. Technical refinements, including premedication for prophylaxis against nausea, vomiting, and epistaxis, were made as a result of early experiences with this technique. Results from the first 100 patients to undergo the Awake TLIF demonstrated durable clinical benefit beyond one year postoperatively. Operating time, blood loss, and hospital length of stay averages well below those generally seen with conventional MIS TLIF. Patients achieved a significant reduction in Oswestry Disability Index from baseline of −12.3 points (P